ANALYSIS OF THE EFFECTIVENESS OF THE MONETARY POLICY TRANSMISSION CHANNEL IN INDONESIA WITH A SINGLE TARGET OF INFLATION FOR THE PERIOD 2016:08 - 2022:12 - Putri Fadilah; Sri Yani Kusumastuti (Media Ekonomi, 2023)
The purpose of this study is to determine The Monetary Policy Transmission Channel In Indonesia With A Single Target of Inflation For The Period 2016:08 - 2022:12. The research method used the Vector Error Correction Model (VECM) for the period August 2016 until December 2022. This study uses secondary data from the Indonesian Central Statistics Agency (BPS) and CEIC (a company providing financial and macroeconomic indicator data). The results of this study show that inflation responses to the shock of variables in the Monetary Channel, Interest Rate Channel, and Inflation Expectation Channel is not very much. Viewed from the result of the Impulse Response Test and Variance Decomposition, the three channels for monetary policy transmission (monetary channel, interest rate channel, and expectation channel) must be more effectively implemented in Monetary Policy decision-making in Indonesia. The interest rate channel is the most effective channel among the three channels. The results of the Impulse Response test and Variance Decomposition prove that inflation responses to the shock of variables in the Interest Rate channel are the strongest and have the least time lag and variance of those variables. The most suitable variable used for an operational target in an interest rate channel is BI-7-Days-Repo-Rate (BI7DR). Based on comparation of the other two variables (deposit rate and interbank money market rate), the results of the Impulse Response test and Variance Decomposition show that BI7DR shock obtains strong and quick inflation responses.